ON ESTIMATES FOR JACOBI-DUNKL TRANSFORM OF DINI-LIPSHITZ FUNCTIONS (Nonlinear Studies, 2016)
In this paper, using a generalised translation operator, we prove some estimates for the Jacobi Dunkl transform in theÂ space $L^{p}(\mathbb{R})$, $(1< p ≤ 2)$, of a class of functions satisfying the Dini-Lipschitz condition.Â